Models of the teacher in biblical texts and their reception - Koet, Bart J.; Ó Floinn, Gearard; Wieringen, Archibald L. H. M. van (Catholic biblical quarterly imprints, 2025)
"What makes a good teacher? From Socrates to John Dewey, educators have long sought to define the essence of teaching and learning. Yet one rich tradition often overlooked in these discussions is the biblical tradition. In Biblical Teachers: Timeless Models for Education and Inspiration, readers are invited to explore a vibrant tapestry of biblical figures and texts that have shaped, challenged, and inspired generations of learners. This volume offers a unique series of encounters with biblical teachers and those who have engaged with their teachings throughout history. Considering a wide array of roles-lecturer, writer, pastor, or even an imaginative medium like a computer game-the book presents a colorful palette of teaching models. These diverse approaches not only reflect the dynamic nature of education but also offer enduring inspiration for educators and learners today"-- Provided by publisher